2007
DOI: 10.4049/jimmunol.179.6.4263
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab-CD20 Complexes Are Shaved from Z138 Mantle Cell Lymphoma Cells in Intravenous and Subcutaneous SCID Mouse Models

Abstract: Infusion of standard-dose rituximab (RTX) in chronic lymphocytic leukemia (CLL) patients promotes rapid complement activation and deposition of C3 fragments on CLL B cells. However, immediately after RTX infusions, there is substantial loss (shaving) of CD20 from circulating malignant cells. Because shaving can compromise efficacies of anticancer immunotherapeutic mAbs, we investigated whether shaving occurs in SCID mouse models. Z138 cells, a B cell line derived from human mantle cell lymphoma, were infused i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
49
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 66 publications
6
49
1
1
Order By: Relevance
“…In contrast, the high affinity receptor Fc␥RI can rapidly recycle and promote very efficient endocytosis of small IgG-containing immune complexes (67)(68)(69)(70). Our in vitro experiments and findings in mouse models (46,71) suggest that it is this high affinity receptor that is primarily responsible for CD20 shaving when patients receive high doses of RTX, which temporarily saturates the clearance capacity of the body (46).…”
Section: Parallel Findings In the Clinicmentioning
confidence: 80%
“…In contrast, the high affinity receptor Fc␥RI can rapidly recycle and promote very efficient endocytosis of small IgG-containing immune complexes (67)(68)(69)(70). Our in vitro experiments and findings in mouse models (46,71) suggest that it is this high affinity receptor that is primarily responsible for CD20 shaving when patients receive high doses of RTX, which temporarily saturates the clearance capacity of the body (46).…”
Section: Parallel Findings In the Clinicmentioning
confidence: 80%
“…Recently, another mechanism of trogocytosis mediated by Ag/Ab immune complexes and FccRs on acceptor cells was identified (6). This mechanism is well characterized as the phenomenon wherein CD20 molecules on malignant B cells are lost after infusion of the humanized anti-CD20 mAb, rituximab (23,24). In this situation, FccR 1 immune cells, such as monocytes, accept the CD20/anti-CD20 immune complexes from B cells.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the level of the complement defense molecules CD46, CD55, and CD59 on lymphoma cells did not correlate, either negatively or positively, with responses to rituximab (50). A series of comprehensive studies from Taylor and colleagues (51)(52)(53) showed trogocytosis as a potential mechanism of rituximab resistance. Trogocytosis is a process whereby phagocytic cells selectively remove bound Ag/IgG complexes (CD20/rituximab, in this case) from the surface of target cells rather than phagocytose them (51,52).…”
Section: And Ronald Levymentioning
confidence: 98%
“…A series of comprehensive studies from Taylor and colleagues (51)(52)(53) showed trogocytosis as a potential mechanism of rituximab resistance. Trogocytosis is a process whereby phagocytic cells selectively remove bound Ag/IgG complexes (CD20/rituximab, in this case) from the surface of target cells rather than phagocytose them (51,52). Consequently, the target cells are no longer opsonized and are able to escape detection by immune effector cells.…”
Section: And Ronald Levymentioning
confidence: 99%